ANALISIS YURIDIS KEWENANGAN PENYIDIKAN ANTAR LEMBAGA PENEGAK HUKUM DALAM TINDAK PIDANA KORUPSI - Barahama, Matrial; Timomor, Adensi; Novy Tuwaidan, Arthur (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
The eradication of corruption requires a special legal approach involving key law enforcement agencies such as the Police, the Prosecutor’s Office, and the Corruption Eradication Commission (KPK). However, overlapping investigative authorities among these institutions cause conflicts and hinder the effectiveness of corruption eradication efforts. By using normative legal approach, this research indicate the need for clear clarification and strict limitation of investigative powers, as well as a strong coordination mechanism, to ensure effective and synergistic law enforcement. The professionalism and independence of the Police are key factors in carrying out investigative duties but require clear regulatory support and oversight. Institutional reform, capacity building of human resources, and regulatory harmonization are crucial to establishing a criminal justice system that is fair, transparent, and free from corruption, thereby restoring public trust and advancing the nation.